2011
DOI: 10.1111/j.2042-3292.2010.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three preoperative skin preparation techniques in ponies

Abstract: Summary The purpose of this study was to evaluate the efficacy of 3 preoperative skin preparations (povidone‐iodine [PI] removed with 70% isopropanol, and 4% chlorhexidine gluconate [CG] removed with either 70% isopropanol [CA] or sterile saline solution [CS]) in ponies. Eighteen ponies were randomly assigned to one of the 3 preoperative skin preparation groups. The skin of ponies was aseptically prepared with PI removed with alcohol, or 4% CG removed with either alcohol or sterile saline solution. The antimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 7 publications
2
25
0
Order By: Relevance
“…37,40 Most of the similar studies had an antiseptic included in the initial presurgical wash. 6,18,40 Our study is the only one to have reported skin reactions after the initial wash with a neutral detergent, and may thereby emphasize the role that washing alone or chemical detergents play in the development of skin reactions. Our study also had a higher prevalence of skin reactions (35%) when compared to other similar studies 6,16,18,40,90 This may be attributed to overzealous washing by inexperienced final year students performing the scrub. Because no dogs showed any significant differences in the grading of the cutaneous reactions between the wash and the application of the antiseptic, and the insignificant distribution of the skin reactions across the antiseptics, it is the author's opinion that the skin reactions were caused by the mechanical wash and not the application of the antiseptics.…”
supporting
confidence: 40%
See 1 more Smart Citation
“…37,40 Most of the similar studies had an antiseptic included in the initial presurgical wash. 6,18,40 Our study is the only one to have reported skin reactions after the initial wash with a neutral detergent, and may thereby emphasize the role that washing alone or chemical detergents play in the development of skin reactions. Our study also had a higher prevalence of skin reactions (35%) when compared to other similar studies 6,16,18,40,90 This may be attributed to overzealous washing by inexperienced final year students performing the scrub. Because no dogs showed any significant differences in the grading of the cutaneous reactions between the wash and the application of the antiseptic, and the insignificant distribution of the skin reactions across the antiseptics, it is the author's opinion that the skin reactions were caused by the mechanical wash and not the application of the antiseptics.…”
supporting
confidence: 40%
“…27 Our study, however, differs from most of the other antiseptic trials in that only one antiseptic preparation procedure was performed. 16,18,37,40,90 The uniform post antiseptic reduction in CFU's of all the products to a median of zero proved that one application of antiseptic only, significantly dropped CFU counts.…”
Section: By Closely Observingmentioning
confidence: 94%
“…We selected a standard 5‐minute CHXG scrub as reference because this method is routinely used in our equine hospital. Although the sustained action of CHXG may be reduced by rinsing with 70% isopropyl alcohol, this protocol is common in many hospitals and other studies . We did not intend to test the residual action of antiseptics and, therefore, adopted this method of rinsing CHXG to maintain clinical applicability.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for microbiological testing is similar to that used in other veterinary studies that have compared the efficacy of antiseptic methods . However, we did not conduct preantiseptic microbiological sampling, which was used in other studies to calculate the percentage of CFU reduction . This design was selected because we sought to compare the activity of 4 skin antiseptic methods, not to establish the final efficacy of the methods in preventing SSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation